Spherically confined H2+: and states. (28th January 2015) - Longo, G Micca; Longo, S; Giordano, D
Abstract: The molecular ion H2 + is studied under strong confinement conditions produced by a spherical barrier centered in the gravity center of the molecule. Results for the potential curves are obtained by diffusion Monte Carlo methods for the ground state (X ) and the first excited state (A ), and reported as functions of the internuclear distance d for different values of the confinement radius. Results show that the compressed states corresponding to both and present deep minima in their potential curves, due to the increased space for electron wave-functions when the protons are displaced from the barrier surface.